A Rare Case of Complete Heart Block in a Young Patient - Zakaria Hindi; Yousef Hindi; Rami Batarseh (Case Reports in Cardiology)
Introduction. Complete heart block (CHB) is considered as one of the dangerous rhythms since it can progress to lethal arrhythmias such as ventricular tachycardia. It can be congenital or acquired. Patients may present with frequent palpitations, presyncope, dyspnea, or chest pain but also may remain asymptomatic. Extensive work-up should be conducted to exclude secondary causes such as infections, cardiac ischemia or myopathies, autoimmune diseases, or endocrinological diseases. In our paper, we would like to present a case of CHB in the setting of aortic abdominal thrombus that nearly occluded both renal arteries. The CHB in this case is thought to be caused by hypertensive cardiomyopathy due to ongoing uncontrolled hypertension, which is caused by bilateral renal artery stenosis. Case Presentation. A 31-year-old male with history of active smoking was incidentally found to have high blood pressure, bradycardia, and CHB on electrocardiogram. The patient was admitted to a cardiology ward and extensive work-up revealed hypokinesia of the left ventricle with low ejection fraction and left ventricle concentric hypertrophy, large abdominal aortic thrombus with bilateral renal artery stenosis, and evidence of arterial collateral connections, which suggest chronicity. The patient then was placed on four antihypertensive medications but eventually, he underwent bilateral renal artery stenting and insertion of permanent pacemaker for his CHB. The patient’s blood pressure then was under control with only one medication, and subsequent CT angiogram showed no evidence of stenosis of both renal arteries. Conclusion. Uncontrolled hypertension can lead to hypertensive cardiomyopathy, which in turn can cause conduction abnormalities such as CHB. Although hypertension can be secondary to a treatable underlying cause, permanent pacemaker is essential to treat CHB.